Study and Application on Test Methodology of Active Antenna System - Fengyi Yang; Tao Yang; Weiliang Xie (Dianxin kexue)
Active antenna system realizes the tight coupling of RF modules and antenna dipoles for the base stations，which makes it difficult to measure AAS RF performance.On the basis of study on several AAS test methodologies such as conducted test，coupling test and far field over-the-air test，AAS RF performance and antenna patterns was tested via combining the conducted test and far field over-the-air test，and the feasibility of combined test methodology was validated，and the reference for the future research on AAS testing was provided.